Tanggung Jawab Pemegang Protokol Notaris Dalam Mengeluarkan Salinan Minuta Akta Yang Terdegradasi - Hasan, Rohmat Esa (Officium Notarium, 2024)
This thesis aims to find out the responsibility of the Notary protocol holder in issuing a degraded copy of the minuta deed. The problem formulated in this study is first how the actions of a notary holding a notary protocol in issuing a minute copy of an incomplete notarial deed are signed by the parties at the minute of the deed, second. What are the responsibilities of the notary protocol holder in issuing a minute copy of the incomplete notarial deed signed by the parties when requesting a deed. This type of research is normative law with statutory and conceptual approaches. The results of this study indicate that first, the actions of a Notary holding a Notary protocol that should be taken is not issuing a copy of the Notary's deed, because the deed is not an authentic deed as referred to as the UUJN, therefore the Notary holding the Notary protocol is not authorized to issue a copy of the deed, but can only make a photocopy according to the original of the deed made by a Notary who submits the Notary's protocol. Second, if the Notary issues a copy of the deed that has not been completely signed by the parties, they may be subject to criminal sanctions for stating on the copy that the deed has been signed perfectly, it can be said that making a false statement. The first suggestion is that the Notary holding the Notary protocol in handing over the Notary protocol must examine carefully at the time of handing over the Notary protocol. Second, the Notary holding the Notary protocol should never issue a copy of the deed that has not been signed by the parties because it can be subject to criminal sanctions.